Hubungan Massa Lemak Tubuh dan Kadar Estradiol Serum pada Wanita Premenopouse di Kota Padang - Virna Zufti Pratiwi; Ulya Uti Fasrini; Yuniar Lestari (Jurnal Ilmu Kesehatan Indonesia, 2021)
Background. Premenopause is a transition period from reproduction to menopause. This phase is characterized by a decrease in estradiol levels which causes body fat mass and cholesterol levels tend to rise in most women of premenopausal age.